JobStart Provides Preemployment Education for Welfare to Work Clients: Methods and Outcomes - Elizabeth B. Bolton (EDIS, 2002)
The JobStart curriculum was developed by Dr. Elizabeth Bolton, Professor of Community Development. Originally developed to address the needs of public housing residents, the curriculum has been adapted and expanded to meet the needs of hard-to-serve WtW clients.